Manganese in teeth and neurobehavior: Sex-specific windows of susceptibility. (November 2017) - Bauer, Julia Anglen; Claus Henn, Birgit; Austin, Christine; Zoni, Silvia; Fedrighi, Chiara; Cagna, Giuseppa; Placidi, Donatella; White, Roberta F.; Yang, Qiong; Coull, Brent A.; Smith, Donald; Lucchini, Roberto G.; et al.
Abstract: Background: Manganese (Mn) is an essential element required for growth and development, but higher body burdens have been associated with neurobehavioral decrements in children. Objectives: We examined whether prenatal or postnatal Mn measured in deciduous teeth was associated with scores on a test of visuospatial learning and memory. Methods: Deciduous teeth were collected from 142 participants (ages 10–14 years) residing near varied ferro‑manganese industry in Italy. Mn concentrations were measured in prenatal and postnatal tooth regions by laser ablation inductively coupled plasma mass spectrometry (ICP-MS). The Virtual Radial Arm Maze (VRAM), an animal-human analogue task, was used to assess visuospatial learning and memory. We used generalized additive, linear and zero-inflated Poisson mixed regression models to estimate associations between prenatal or postnatal Mn concentrations and repeated measures of all four VRAM outcomes: time, distance, working and reference memory errors. Effect measure modification by sex was examined in stratified models. Results: U-shaped associations between prenatal Mn and VRAM outcomes were observed among girls only (pGAMM  = 0.001 to 0.02 in stratified models). Compared to the mid-tertile of prenatal Mn, girls in the highest tertile took 7.7 s [95% CI: − 6.1, 21.5] longer to complete the task, traveled 2.3 maze units [0.1, 4.4] farther, and committed more working and reference memory errors (β for count ratio = 1.33 [1.01, 1.83]; 1.10 [0.98, 1.24], respectively). This association was not observed among boys. In contrast, for postnatal Mn, no significant associations were found, and patterns were similar for boys and girls. Conclusions: The prenatal period may be a critical window for the impact of environmental Mn on visuospatial ability and executive function, especially for females. Highlights: Children are vulnerable to Mn toxicity, yet susceptibility factors are understudied. We measured Mn in teeth to estimate exposure during critical developmental windows. Complex visuospatial ability was measured using an animal task adapted for humans. The prenatal period may be important for Mn effects on girls' visuospatial ability.